Nickel phosphide nanoalloy catalyst for the selective deoxygenation of sulfoxides to sulfides under ambient H2 pressure. Issue 43 (3rd September 2020) - Fujita, Shu; Yamaguchi, Sho; Yamazoe, Seiji; Yamasaki, Jun; Mizugaki, Tomoo; Mitsudome, Takato
Abstract : A titanium-dioxide-supported nickel phosphide nanoalloy (nano-Ni2 P/TiO2 ) functions as a highly active non-precious-metal-based heterogeneous catalyst for the selective deoxygenation of sulfoxides to sulfides under just 1 bar of H2 . Abstract : Exploring novel catalysis by less common, metal–non-metal nanoalloys is of great interest in organic synthesis. We herein report a titanium-dioxide-supported nickel phosphide nanoalloy (nano-Ni2 P/TiO2 ) that exhibits high catalytic activity for the deoxygenation of sulfoxides. nano-Ni2 P/TiO2 deoxygenated various sulfoxides to sulfides under 1 bar of H2, representing the first non-noble metal catalyst for sulfoxide deoxygenation under ambient H2 pressure. Spectroscopic analyses revealed that this high activity is due to cooperative catalysis by nano-Ni2 P and TiO2 .